2022
DOI: 10.3390/pharmaceutics14040797
|View full text |Cite
|
Sign up to set email alerts
|

Drug Nanocrystals for Active Tumor-Targeted Drug Delivery

Abstract: Drug nanocrystals, which are comprised of active pharmaceutical ingredients and only a small amount of essential stabilizers, have the ability to improve the solubility, dissolution and bioavailability of poorly water-soluble drugs; in turn, drug nanocrystal technology can be utilized to develop novel formulations of chemotherapeutic drugs. Compared with passive targeting strategy, active tumor-targeted drug delivery, typically enabled by specific targeting ligands or molecules modified onto the surface of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…This category also includes cancer imaging and diagnosis such as the MRI imaging agent Resovist, carboxydextran-coated superparamagnetic iron oxide nanoparticles approved for liver contrast-enhanced MRI102 [ 87 ]. Another 10% are nanocrystals, such as Tricor (approved in 2004) or Triglide (approved in 2005), used to improve the bioavailability of the anti-hypercholesterolemic fenofibrate [ 88 89 ].…”
Section: Reviewmentioning
confidence: 99%
“…This category also includes cancer imaging and diagnosis such as the MRI imaging agent Resovist, carboxydextran-coated superparamagnetic iron oxide nanoparticles approved for liver contrast-enhanced MRI102 [ 87 ]. Another 10% are nanocrystals, such as Tricor (approved in 2004) or Triglide (approved in 2005), used to improve the bioavailability of the anti-hypercholesterolemic fenofibrate [ 88 89 ].…”
Section: Reviewmentioning
confidence: 99%
“…First, the modification of photosensitizers with biological conjugates, such as peptide or antibody conjugates, facilitates targeted delivery specifically to tumors . Second, the chemical conjugation of photosensitizers within delivery nanocarriers enhances the efficient transport of drugs from the administration site to the target tissue. , Moreover, in active targeting systems, targeting ligands on the surface of nanocarriers results in increased cellular uptake by receptor-mediated endocytosis and therefore increased photosensitizer accumulation in cancer cells. This approach holds promise in addressing various limitations associated with photosensitizers, including a lack of tumor selectivity, poor bioavailability, and unfavorable biodistribution . Furthermore, the unique microenvironment within tumors, including elevated levels of intracellular glutathione (GSH), overexpressed enzymes, reactive oxygen species (ROS), and an acidic pH, provides an opportunity to develop specific triggers for photosensitizers to enhance tumor therapy. , Consequently, the development of targeted stimuli-responsive photosensitizer-conjugate-based nanoparticles is highly promising for achieving targeted and effective tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…They also possess the outstanding properties of high drug loading, low toxicity, simple preparation process, and wide application ( Kalhapure et al, 2022 ; Ma et al, 2023 ; McGuckin et al, 2022 ; Shen et al, 2016 ). In the early development stages, NCs were primarily used to improve the oral bioavailability of drugs with poor water solubility ( Gao et al, 2013 ), but they currently have been expanded to other various drug delivery systems including parenteral, transdermal, pulmonary, ocular and targeted drug delivery, etc ( Jacob et al, 2020 ; Lu et al, 2022 ; Mohammad et al, 2019 ). Drug NCs with modified physicochemical properties for targeted drug delivery could maintain a potent therapeutic concentration to produce desirable pharmacological effect due to their high drug loading ( Zingale et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, some stabilizers can maintain the stability of drug NCs, while also affect the in vivo performances of drug NCs ( Qin et al, 2022 ; Soisuwan et al, 2019 ), which can be considered as functional stabilizers. Moreover, active targeted drug delivery can be achieved via surface modification of drug NCs by functional stabilizers with the ability to specifically target surface receptors ( Lu et al, 2022 ; Zingale et al, 2022 ), as drug NCs were demonstrated to be long biological life in the body following intravenous delivery ( Hang et al, 2022 ; Shen et al, 2021a ; Wang et al, 2018 ). Transferrin modified docetaxel NCs significantly improved the cellular uptake and cytotoxicity of docetaxel in A549 cell line via interacting with transferrin receptors that are higher expressed in cancer cells, achieving tumor targeting drug delivery ( Choi and Park, 2017 ).…”
Section: Introductionmentioning
confidence: 99%